Kajian Pembelajaran Online Berbasis Wiki Di Lingkup Perguruan Tinggi - Soetam Rizky Wicaksono (Journal of Education and Learning (EduLearn), 2012)
Scope of online learning in higher education now more widely assumed to be a repository of teaching materials for both teachers and students. Nevertheless there are still many things that can still be developed and studied with an experimental model for online learning can be more participatory in the learning context given that the scope of the college is more directed to andragogik. One innovation that leads to this is to make the application of model-based learning wiki adopting crowdsourcing. This paper explores theoretical study attempted as a first step in the research development of wiki-based online learning model. The results of this study should be the basis for experiments to be conducted in order to adapt contextually in real state.